The Influence of Cross Selling and Up Selling in Increasing Customer Loyalty - Restu Tanjung, Dwi; Ikhsan Harahap, Muhammad; Anggraini, Tuti (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
Business competition between banks now shows increasingly tight competition to get customers, so banks are struggling to provide the best services and services. This research aims to find out whether there is an influence of Cross-Selling and up-selling in increasing customer loyalty at Bank Syariah Indonesia (BSI) KC Kuala Simpang. This research was conducted at BSI KC Kuala Simpang. This type of research uses quantitative methods, which collect data in the form of questionnaires that are distributed to users or customers of BSI KC Kuala Simpang. The population in this study was 1,200 customers with a sample size of 100. To determine the number of samples taken, the Slovin formula was used. Meanwhile, the analysis technique uses SPSS 25 software, which explains that the Cross Selling and up Selling variables have a positive and significant influence on customer loyalty. Cross-selling and up-selling are two strategies that companies often use to increase sales and increase customer satisfaction. Although they are two different techniques, they are closely related and often work together to maximize sales potential. Both strategies have the same goal, namely increasing the average transaction value per customer. Cross-selling involves selling additional products that are complementary or related to what the customer has already purchased, when it comes to up-selling, the aim is to persuade customers into buying a higher-priced or deluxe version of the product they initially planned to buy.